Murāqabah in practice: An ethnographic analysis of the Minangkabau Islamic Mato profit-sharing system in an urban Padang restaurant - Rizki, Mulyani; Rusli, Ris’an; Barkah, Qodariah (Journal of Islamic Economics Lariba, 2025)
IntroductionIndigenous profit-sharing arrangements rooted in Islamic ethics remain understudied, despite their prominence in Southeast Asian enterprises. The Minangkabau Mato system, practised in Padang restaurants, melds Qurʾānic ideals of justice with kin-based solidarity and continuous spiritual self-monitoring (murāqabah). Understanding whether such a relational model can thrive in competitive urban markets is critical for both cultural preservation and Islamic economic theory.ObjectivesThis study aims to (1) document in detail how Mato is implemented in a diaspora restaurant setting, (2) assess its economic and motivational effects relative to formal mudharabah contracts, and (3) evaluate the role of murāqabah as an endogenous governance mechanism.MethodAdopting an ethnographic design, the researcher spent twenty-four weeks immersed in a medium-sized Padang restaurant in Palembang. Data comprised participant observation during daily operations, twenty-three semi-structured interviews covering all functional roles, and an analysis of daily balance sheets and archival photographs. Transcripts and field notes were coded inductively and deductively in NVivo, yielding four integrative themes: Islamic-ethical foundations, sociocultural integration, worker perceptions, and cultural-preservation dynamics.ResultsTransparent daily splits and flexible profit ratios foster high psychological ownership, intrinsic motivation, and negligible staff turnover. The employees cited murāqabah as a powerful internal control that reduced opportunism and reinforced meticulous bookkeeping. During a nine-percent spike in commodity costs, consensual ratio adjustments prevented wage arrears—an agility unattainable under fixed-ratio mudharabah schemes. Branding Mato as “Profit-Sharing the Minangkabau Way” simultaneously enhanced customer loyalty and safeguarded cultural identity.ImplicationsThe findings position Mato as a viable template for community-based Islamic finance and highlight the policy need for legal pluralism that legitimizes indigenous models without eroding their relational strengths. Managers seeking value-aligned incentives may replicate daily open-table reconciliations, ratio elasticity, and devotional briefings to embed trust and resilience.Originality/NoveltyThis study provides the first in-depth ethnographic evidence of Mato in an urban service enterprise, demonstrating how murāqabah and flexible sharing ratios translate Islamic moral philosophy into day-to-day business sustainability, while advancing heritage-based competitive advantage.